Sikap Skeptik Rasul Thomas Sebagai Model Dealektika Kritis Di Era Post-Truth - Kandunmas, Fransikus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2024)
Members of modern society receive a lot of news that is not true or even lies, but strangely, society easily accepts the news. This phenomenon occurs in a modern era that experts call post-truth. Initially, this phenomenon was used more for political interests but then spread to various areas of society's life. There are similarities between post-truth and hoax news (fake news) because both are wrapped in shocking headlines and are able to attract public attention, even though they are not balanced with data and facts, maybe even using fake data whose truth is unclear. This paper is a literature study with a descriptive-critical approach to the sceptical attitude of the Apostle Thomas and its implications for society in the post-truth era. The main question of this research is “how does Thomas’s perspective become a dialectical-critical paradigm in dealing with the problem of hoaxes in modern times?” The main objective of this paper is to explain Thomas’ sceptical attitude as a model of critical reasoning dialectics as an inspiration for assessing the problem of hoaxes in the post-truth era.